Total Phenolic Content and Anti-oxidant Capacity of Some Spices and Herbs Grown in Vietnam - Khue, Dang Bui; Tuan, Pham Minh; Quan, Ngo Van; Oanh, Dang Thi Bui (Journal of Postharvest Technology, 2013)
In recent years, the obesity and oxidative stress are the most common factors affecting the human health. Especially, the rancid foods are plentiful with free radicals, which trigger chronic diseases such colon cancer, breast cancer, heart diseases and so on. Therefore, this study focuses on the determination of the levels and activities of polyphenols extracted from some spices and herbs applied to traditional Vietnamese foods. The results categorized these plant materials into 3 sub-categories including one group shows the high total phenolic content and antioxidative ability (green tea leaves, green guavas and buffalo spinach leaves). The second group has low total phenolic content, but high in antioxidant capacity (tungho leaves, onion, elsholtzia leaves, green mangoes, basil leaves, lemongrass leaves, coriander leaves, green amberella, turmeric roots, ginger roots, galangal roots) and the last group possessed the lowest total phenolic content and antioxidant activity (lemon leaves).